2020
DOI: 10.3390/bs10110167
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Depressive Symptoms in Children and Youth with and without Cerebral Palsy: A Pilot Study

Abstract: Children with cerebral palsy (CP) often exhibit mental health problems, such as depressive symptoms. The purpose of this study was to describe the self-rated depressive symptoms in children with and without CP and to investigate the associated predictors. Participants included 24 children with CP and 33 typically developing (TD) children. Depressive symptoms were assessed using the Birleson Depression Self-Rating Scale for Children. Parents of the participants completed the Strengths and Difficulties Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The parent version of the Strengths and Difficulties Questionnaire was used to assess students’ psychological attributes [ 30 ]. The scale was composed of 25 items covering negative and positive attributes; each item was answered with either “not true=0,” “somewhat true=1,” and “certainly true=2.” The scale included emotional symptoms, behavior problems, hyperactivity or inattention, peer relationship problems, and pro-social behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parent version of the Strengths and Difficulties Questionnaire was used to assess students’ psychological attributes [ 30 ]. The scale was composed of 25 items covering negative and positive attributes; each item was answered with either “not true=0,” “somewhat true=1,” and “certainly true=2.” The scale included emotional symptoms, behavior problems, hyperactivity or inattention, peer relationship problems, and pro-social behavior.…”
Section: Methodsmentioning
confidence: 99%
“…The parent version of the Strengths and Difficulties Questionnaire was used to assess students' psychological attributes [30]. The scale was composed of 25 items covering negative and positive attributes; each item was answered with either "not true=0," "somewhat true=1," and "certainly true=2."…”
Section: Psychological Attributesmentioning
confidence: 99%
“…Other factors that could be considered in the future to explain the variation include measuring if AYA with CP have meaningful participation at work and in recreation activities, social isolation, and stress associated with school, work, peer relationships, managing finances, and making health care decisions [ 54 ]. A decline in social participation can also contribute to a decline in mental health [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the restriction of various daily and outdoor activities can lead to mental health problems, such as depressive symptoms, in children with CP [ 22 ]. Particularly, decline of activities and enjoyment in their daily life was identified as a contributing factor to greater severity of depressive symptoms [ 23 ]. Therefore, it is necessary to pay attention to changes in mental health and behavior and take appropriate action as soon as signs are detected in such children.…”
Section: Discussionmentioning
confidence: 99%